Designing a Human Machine Interface for Quality Assurance in Car Manufacturing: An Attempt to Address the “Functionality versus User Experience Contradiction” in Professional Production Environments - Nikolaj Borisov; Benjamin Weyers; Annette Kluge (Advances in Human-Computer Interaction)
The complexity of nowadays car manufacturing processes increases constantly due to the increasing number of electronic and digital features in cars as well as the shorter life cycle of car designs, which raises the need for faster adaption to new car models. However, the ongoing digitalization of production and working contexts offers the chance to support the worker in production using digital information as well as innovative, interactive, and digital devices. Therefore, in this work we investigate a representative production step in a long-term project together with a German car manufacturer, which is structured into three phases. In the first phase, we investigated the working process empirically and developed a comprehensive and innovative user interface design, which addresses various types of interactive devices. Building up on this, we developed the device score model, which is designed to investigate interactive system and user interface in production context due to ergonomics, UI design, performance, technology acceptance, and user experience. This work was conducted in the second phase of the project, in which we used this model to investigate the subjective suitability of six innovative device setups that implement the user interface design developed in phase one in an experimental setup with 67 participants at two locations in south Germany. The major result showed that the new user interface design run on a smart phone is the most suitable setup for future interactive systems in car manufacturing. In the third and final phase, we investigated the suitability of the two best rated devices for long term use by two workers using the system during a full shift. These two systems were compared with the standard system used. The major conclusion is that smartphones as well as AR glasses show very high potential to increase performance in production if used in a well-designed fashion.